THE IMPACT OF RENEWABLE ENERGY CONSUMPTION ON CARBON DIOXIDE EMISSIONS - THE CASE OF SOUTH AMERICAN COUNTRIES - Koengkan, Matheus da Costa; Fuinhas, José Alberto (Revista Brasileira de Energias Renováveis, 2018)
The impact of renewable energy consumption on the carbon dioxide emissions was analyzed for a panel of ten South American countries in a period from 1980 to 2012. The Autoregressive Distributed Lag Methodology was used in order to decompose the total effect of renewable energy consumption on the carbon dioxide emissions in its short- and long-run components. The results indicate that the consumption of renewable energy reduce the carbon dioxide emissions in -0.0420 % when the consumption of alternative sources increases in 1% in short-run. The empirical evidence shows that the renewable consumption plays an important role in reducing CO2 emissions and that the economic growth and energy consumption in the South American countries are still based on fossil fuels. Keywords: Environmental, Energy economics, Econometric.